Imperial Adjudication in Late Antiquity: Evolutions and Perceptions in the Light of Documentary Evidence - Luisa ANDRIOLLO (Studia Historica: Historia Antigua, 2020)
This paper explores the functions of recorded proceedings in late antique court administration, focusing on documentary records related to imperial adjudication. Verbatim records of verdicts uttered by the emperor on individual cases are on the whole scarcely attested; they become particularly rare from the mid-3rd century AD, and are no longer preserved after the 4th century. The author scrutinizes the causes and meaning of such a state of evidence. After an in-depth analysis of the extracts of proceedings included in the Theodosian and Justinian codes, parallel literary and non-literary sources on imperial jurisdiction in the 4th and 5th centuries are considered. The discussion highlights changes occurred in the function, circulation and reception of minuted records. These reflect evolutions which affected not only judicial procedure, but also the understanding of the imperial role, the forms of institutional communication, and late antique legal thinking.